Zn anode surface engineering for stable zinc-ion batteries: Carbon dots incorporated mesoporous TiO2 as a coating layer - Song, Tian-Bing; Ma, Qian-Li; Zhang, Xi-Rong; Ni, Jia-Wen; He, Tian-Le; Xiong, Huan-Ming (Chemical engineering journal (Lausanne, Switzerland : 1996), 2023)
•This protective layer is constructed by TiO2 nanosheets and N-doped carbon dots.•The TiO2 layer can immobilize water molecules and prevent the side reactions.•NCDs with abundant functional groups provide the zincophilic nucleation sites.•The Zn-TiO2/NCDs||MnO2 full cells show an excellent reversibility at 2 A/g. Uncontrolled Zn dendrites growth and sustained corrosion originating from severe interfacial reactions are the major shortcomings of Zn metal electrodes in aqueous zinc-ion batteries (ZIBs). In order to overcome these obstacles, we designed a protective coating layer to stabilize the zinc anode and regulate the Zn deposition simultaneously. This hybrid layer (TiO2/NCDs) is constructed by mesoporous TiO2 nanosheets and N-doped carbon dots (NCDs), which is prepared by a solvothermal growth under the control of NCDs. On one hand, the TiO2 layer immobilize water molecules effectively, preventing them from the parasitic reactions with Zn electrodes. On the other, NCDs with abundant functional groups (–OH, –COOH, –NH2) provide the zincophilic nucleation sites to endow a small deposition overpotential of 28 mV and guide Zn deposition into a petal structure. Owing to mesoporous protective coating layer, the Zn-TiO2/NCDs anode presents a low voltage hysteresis of 48 mV and a prolonged cycling lifespan of 1500 h at 5 mA cm−2 and 2.5 mAh cm−2. Moreover, aqueous ZIBs assembled with the Zn-TiO2/NCDs anode and the α-MnO2 cathode show outstanding reversibility and good cycling stability, whose capacity retention is up to 90% after 1000 cycles.